FLIP BOOK BASED DIGITAL MODULE GUIDELINES FOR PREPARING PRACTICE REPORTS FOR TOURISM POLYTECHNIC - Yuke Hernawati; Abdul Rozak; Yusida Gloriani (Bajang Institute, 2023)
This research was conducted with the aim to find out how the process of developing Flip Book-based learning media and aims to produce Flip Book-based learning media products. This learning media is made to facilitate teaching and learning activities for educators and students. With this learning media students are more enthusiastic in teaching and learning activities. This research is a Design Based Research (DBR) development research which refers to Sugiyono's development model, which uses seven steps in research, namely 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Improvement Design, 6) Product Testing, 7) Product Revision. Data collection techniques in this study used validation questionnaires, namely validation of material experts and media expert validation as well as student and lecturer responses. Data collection techniques in this study consisted of interviews (interviews) with students or lecturers of the Indonesian Language Course